2012
DOI: 10.3920/bm2012.0012
|View full text |Cite
|
Sign up to set email alerts
|

Growth advantage of Streptococcus thermophilus over Lactobacillus bulgaricus in vitro and in the gastrointestinal tract of gnotobiotic rats

Abstract: The yoghurt bacteria, Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus, are alleged to have beneficial effects on human health. The objective of this study was to characterise growth, biochemical activity and competitive behaviour of these two bacteria in vitro and in vivo. S. thermophilus LMD-9 and L. bulgaricus ATCC 11842 growth and lactate production were monitored in different media and in the gastrointestinal tract (GIT) of germ-free rats. In vitro, particularly in milk, S. thermop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…In the case of strict anaerobes like F. prausnitzii , their ability to colonize is governed by the physicochemical constraints of gut rather than by any lack of metabolic substrates. This contrasts with Lactobacillus bulgaricus , which is an aerobic-tolerant lactic acid bacterium, and which does not colonize the gut of GF rats in the absence of lactose [48]. That colonization by B. thetaiotaomicron precedes the implantation of F. prausnitzii gives clues about mechanisms governing microbial ecology and processes of colonization.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of strict anaerobes like F. prausnitzii , their ability to colonize is governed by the physicochemical constraints of gut rather than by any lack of metabolic substrates. This contrasts with Lactobacillus bulgaricus , which is an aerobic-tolerant lactic acid bacterium, and which does not colonize the gut of GF rats in the absence of lactose [48]. That colonization by B. thetaiotaomicron precedes the implantation of F. prausnitzii gives clues about mechanisms governing microbial ecology and processes of colonization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of the three species to survive the passage through the gastrointestinal tract was not certain. Indeed a recent study shows that L. bulgaricus ATCC 11842 was not able to set up when administered alone or with S. thermophilus LMD9 [36]. Previously we showed that the three strains were considered tolerant to bile salts but had different survival abilities at low pH [8].…”
Section: Discussionmentioning
confidence: 87%
“…bulgaricus declined from 7 to 6 log CFU/g in yogurt during storage period of 28 days. These findings might also be explained by the competitive and growth advantage that S. thermophilus shows over L. bulgaricus [44] [45]. The highest counts of Lactobacillus bulgaricus LB-12 were observed at days 1 and 14 of storage (…”
Section: Lactobacillus Delbrueckii Ssp Bulgaricus Lb-12mentioning
confidence: 98%